Isolation of gram-negative bacteria from metacarpal injury of Panthera tigris sumatrae trapped in Subulussalam, Indonesia - . Darmawi; . Darniati; Zakiah Heryawati Manaf; . Syafruddin; Arman Sayuti (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The present study aimed to isolate gram-negative bacteria infected metacarpal of Panthera tigris sumatrae trapped in Subulussalam, Aceh Province. Swab sample was obtained from metacarpal injury of P. tigris sumatrae. Swab sample was cultured to nutrient broth media using sterile cotton swabs or Pasteur pipettes, and incubated at 37°C temperature for 24 hours. Culture was spared on MacConkey media and incubated again at 37°C temperature for 24 hours. Determination of bacteria colony growth on the surface of MacConkey media based on shape, colour, surface, size, and viscosity (consistency). The bacteria colony stained with Gram staining, and tested biochemically.  The result showed that gram-negative bacteria such as Citrobacter sp., Proteus sp., Providencia sp., Pseudomonas sp.,and Salmonella sp. isolated from metacarpal injury of P. tigris sumatrae.